The Effect of Price and Delivery Timeliness on Customer Satisfaction at Tiki Agent Kebon Kacang Branch - Raza, Erwin; Amin, Muhammad Ibrahim; Pratama, Teuku Arya Yogie; Andiara, Muhammad Daffa; Permata, Ananda Niken Ayu (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This research aims to investigate the influence of price and delivery timeliness on customer satisfaction in the delivery services of TIKI Kebon Kacang Branch in 2024. A quantitative research method was employed, with data collection conducted through a questionnaire survey. The sampling technique used probability sampling with an accidental random sampling approach, involving 94 respondents. Data analysis was performed using SPSS version 26. The results indicate that price does not have a significant effect on purchase satisfaction, while delivery timeliness has a positive and significant influence. Simultaneous testing reveals that both price and delivery timeliness together have a positive and significant impact on customer satisfaction.